Degrees of Givenness : On Saturation in Jean-Luc Marion - Gschwandtner, Christina M., 1974- (Book collections on Project MUSE., 2014)
The philosophical work of Jean-Luc Marion has opened new ways of speaking about religious convictions and experiences. In this exploration of Marion's philosophy and theology, Christina M. Gschwandtner presents a comprehensive and critical analysis of the ideas of saturated phenomena and the phenomenology of givenness. She claims that these phenomena do not always appear in the excessive mode that Marion describes and suggests instead that we consider degrees of saturation. Gschwandtner covers major themes in Marion's work-the historical event, art, nature, love, gift and sacrifice, prayer, an.